Optimization of formulation composition of health whey–based beverage - Ткаченко, Наталія Андріївна; Некрасов, Павло Олександрович; Вікуль, Світлана Іванівна (Eastern-European Journal of Enterprise Technologies, 2016)
The development of industrial production of cheese and casein in the world gives rise to the whey use problem. The need to solve this problem is caused by technological and environmental aspects. Whey is almost not processed in Ukraine. Therefore, the development of health whey-vegetable beverages with optimal component composition is an urgent task. The paper presents the classification and characteristics of whey types, justifies the choice of vegetable raw materials - Tagetes patula, as a source of biologically active substances, substantiates the usefulness of berry fillers in beverages. Rational parameters of the extraction process of biologically active substances from Tagetes patula flowers by drinking water: temperature (95±5) °C, duration 60 min, water duty 10 are established. The optimal ratio of whey, tincture of Tagetes patula flowers and berry filler "Wild berry" – 73.8; 18.5 and 6.2 %, respectively, as the components of the whey-vegetable basis for the production of health beverages is found. The chemical composition and quality indicators of the developed whey-vegetable basis with the optimal component composition are determined. The recommendations on developing the technologies of three groups of non-fermented and fermented health whey-vegetable beverages with high probiotic, antioxidant and hepatoprotective properties are given.